Modifications of the PI3K/Akt/mTOR axis during FeHV-1 infection in permissive cells - Ferrara, Gianmarco; Longobardi, Consiglia; Damiano, Sara; Ciarcia, Roberto; Pagnini, Ugo; Montagnaro, Serena (Frontiers in Veterinary Science, 2023)
FeHV-1 is the causative agent of infectious rhinotracheitis in cats. The relationship between viral infection and the PI3K/Akt/mTOR pathway, as well as its function in crucial physiological processes like as autophagy, apoptosis or the IFN induction cascade is known for other varicelloviruses. . However, there is no information on whether autophagy is activated during FeHV-1 infection nor on how this infection modifies PI3K/Akt/mTOR pathway. In this work, we aim to elucidate the involvement of this pathway during cytolytic infection by FeHV-1 in permissive cell lines. Using a phenotypic approach, the expression of proteins involved in the PI3K/Akt/mTOR pathway was examined by Western blot analysis. The findings demonstrated the lack of modifications in relation to viral dose (except for phospho-mTOR), whereas there were changes in the expression of several markers in relation to time as well as a mismatch in the time of activation of this axis. These results suggest that FeHV-1 may interact independently with different autophagic signaling pathways. In addition, we found an early phosphorylation of Akt, approximately three hours after infection, without a concomitant decrease in constitutive Akt. This result suggests a possible role for this axis in viral entry. In a second phase, the use of early autophagy inhibitors was examined for viral yield, cytotoxic effects, viral glycoprotein expression, and autophagy markers and resulted in inefficient inhibition of viral replication (12 hours post-infection for LY294002 and 48 hours post-infection for 3-methyladenine). The same markers were examined during Akt knockdown, and we observed no differences in viral replication. This result could be explained by the presence of a protein kinase in the FeHV-1 genome (encoded by the Us3 gene) that can phosphorylate various Akt substrates as an Akt surrogate, as has already been demonstrated in genetically related viruses (HSV-1, PRV, etc.). For the same reasons, the use of LY294002 at the beginning of infection did not affect FeHV-1-mediated Akt phosphorylation. Our findings highlight changes in the PI3K/Akt/mTOR pathway during FeHV-1 infection, although further research is needed to understand the importance of these changes and how they affect cellular processes and viral propagation